La modalidad dialéctica y otras categorías de modalidad dual (o complementaria) en algunos géneros discursivos - Ruiz, Marcela; Zenteno, Carlos (Boletín de Filología, 2004)
A first aim of the present study is to account for the operation of the ‘dialectical mode of discourse’, which makes manifest a higher-orderconfigurational discoursal-textual construct here identified as the ‘dual’, or ‘complementary’, mode of discourse. To this effect, two main actions are implemented: First, a description is presented of the semantico-pragmatic functions of the dialectical mode at the discoursal level underlying the surface linguistic text. Then, an inventory is provided of some subsets of lexical and syntactic resources realising the dialectical mode within the corresponding textual organization. In a complementary manner, the study also aims at proposing the existence of some alternative configurational dual modes, the ‘analogical mode’ and the ‘discoursal metaphor’, both also operating at text and discourse levels.The descriptive tasks carried out involved, mainly, the examination and analysis of some textual samples selected from a corpus of approximately 100 Chilean Spanish texts, all of which are representatives of the written journalistic discourse genre, mainly editorials, opinion articles, as well journalistic essays and brief expository articles.